Potential of African Sustainable Renewable Energy – A View on Photovoltaic Options for Sub-Saharan Energy Shortage - (:unkn) unknown (My University, 2024)
Africa, despite being referred to as the “Sun continent”, Africa has the largest population with no access to electricity. This continent is striving towards its industrialisation, yet the chronic shortage of electrical power, fundamentally hampers the development of its countries. Regardless of the abundance of almost all natural resources, Africa is still unable to sustain basic living needs due to lack of energy, and, most households rely on biomass for cooking. This work reviewed energy problem and used Africa solar radiation intensity map to estimate the potential energy generation from the sun. Here four scenarios are played for Angola, Chad, Somalia and Zimbabwe, randomly selected to illustrate different intensity of sun irradiation. This paper used the PVGIS tool provided by the European Commission to simulate and estimate potential energy generation from the sun alone, and using 1kWp Solar PV panel, scenarios of potential of energy generation were modelled. The results showed that one unit could generate up to 1704.70kWh/year in Muqdishu, 1749.96 kWh/year in Ndjamena, 1635.62kWh/year in Huambo and 1704.70kWh/ year in Harare.
Keywords: African Research